The role of Toxoplasma gondii in concentration of some sex hormones in infertile individual - Al-Ardi, Musafer Hindi (Journal of medical and pharmaceutical sciences, 2021)
The main objective: Link the incidence of the Toxoplasma gondii present and manifestations of some sex hormones ‎ at ‎infertile persons.‎Follicle-stimulating hormone (FSH), 17-β Estradiol (E2), and testosterone are key ‎regulators for the development ‎and progress of germline cells. Also affect many defensive ‎functions to the ‎immune system. Toxoplasma gondii attempts to manipulating these ‎Hormones concentration to their survive. ‎‎The study methodology‎‏:‏‎ since October 2018 tell 31th March 2019, 100 samples of the blood of ‎infertile ‎patients have been collected from both sexes from outpatient clinics in ‎different areas of ‎Qadisiyah governorate, Iraq. All there examined with Elisa test to detect IgM and IgG ‎antibodies against T. gondii and to estimate concentration of sex hormones. ‎Results: ‎ 39 samples (39 %) were positive to T. gondii. IgM positive ‎samples were (6 and ‎‎10) with (12% and 20%) at male and female, Positive IgG samples for male ‎and female were (10 and 13) ‎with (20% and 26%).‎ In male, Testosterone ‎concentrations were increased in infected where were (5.4 and 5) ng/ ml with IgG and IgM ‎test. Also E2 were (33.6 and 35) pg/ ml with IgG and IgM infected men ‎. While FSH concentrations were decreased in (12.1 and 12.3) IU with IgG and ‎IgM. In female, FSH and E2 concentrations were increased in infected female, ‎where were (5.45 and 5.9)IU/ ml and (260 and 250)pg/ ml from both hormones with IgG ‎and IgM test. Testosterone concentration was decreased (0.98)ng/ ml with IgG, ‎but increased (1.35) ng/ ml with IgM in female. ‎‎The study has been showed that a significant difference in the concentrations ‎of hormones studied ‎between non-infected and infected samples in ‎the acute case, and did not register a ‎significant difference between ‎chronic infection and non-infection, a significant increase ‎in ‎hormones Testosterone and E2 in male and female while FSH in ‎female only, FSH ‎concentration was lower in male after infection.‎Conclusion: in light the study results the author see that: Infection with the parasite is associated with significant changes ‎in the ‎concentrations of sex hormones in infertile peoples, therefore ‎it can be said that infection ‎with Toxoplasma gondii is one of the ‎main causes of infertility in both sexes.‎ ‎‎Suggestions:‎‎Conduct broader studies by examining more people and ‎determine the relationship ‎between infertility and sex hormone ‎concentration with infection by T. gondii in girls and ‎boys before ‎or after puberty.‎
Keywords: Toxoplasma gondii; fertility; sex hormones; Elisa